Novel Mesoporous Silica Materials with Hierarchically Ordered Nanochannel: Synthesis with the Assistance of Straight-Chain Alkanes and Application - Haidong Zhang; Xiaohong Li (Journal of Chemistry, 2016)
The straight-chain alkane-assisted synthesis of hierarchical mesoporous silica materials (MSM) results in variable mesostructures and morphologies due to remarkably different self-assembly routes of template agent from those without the assistance of straight-chain alkanes. The textural properties, particularly pore size, channel structure, morphology, and hierarchical structure of those MSM make them demonstrate peculiar effects in the immobilization of homogeneous catalysts.